“Amma” or “Mommy” : the role of mothers in facilitating intergenerational language transmission in the Singaporean tamil community - Nageswaran Naganandhini. (2012)
This paper aims to obtain an overview of the language use patterns and language attitudes of Singapore Tamil mothers with or in the presence of their children. The Tamil language has been observed to be rapidly losing ground in Singapore with the dominance of English and there have been efforts on the part of the government to promote use of the language. However, these efforts are focused on the domains of education and media and the home domain has not received much attention. Since the home domain is said to be the most important for the maintenance of minority language and the significance of the mothers’ role, in particular, in facilitating this has been proven through past studies, this study focuses on the mother’s language input and attitudes. A total of 22 respondents, aged between 25 and 44 and with children at or within the age of 6, were surveyed using a questionnaire. They were asked to rate their language use for different domains to see their language use patterns in direct and indirect language input situations. They were also asked open-ended questions that elicited their language attitudes towards Tamil. The results showed a clear dominance of English in most domains expect in the interactions with parents/parents-in-law and guests. It was noted that even though they had a positive attitude towards the Tamil language and claimed to believe that their child should be fluent in his/her mother tongue, this was not reflected in their English dominated language use patterns with the child. Education level of the mothers proved to show a difference in language behavior with the non-university educated mothers using more English and lesser Tamil than the university-educated mothers. The implications of this are that covert negative attitudes towards the Tamil language that has contributed to its subordination in the home domain raises serious concerns about the future presence of the language, or the possible lack of it, in Singapore. This paper concludes that there is a need for the promotion of Tamil language use in the home and family domains.